Cardiovascular Disease Risk Factors in Québec Male Firefighters. Issue 6 (June 2018) - Gendron, Philippe; Lajoie, Claude; Laurencelle, Louis; Trudeau, François
Abstract : Objective: We aimed to document the prevalence of cardiovascular disease (CVD) risk factors and symptoms in Québec firefighters. Methods: Seven hundred and seventy-nine (779) male firefighters (age: 41.6 ± 10.4 years; body mass index [BMI]: 28.0 ± 3.6 kg/m 2 ) answered an online questionnaire evaluating lifestyle and the presence of CVD risk factors and symptoms. Results: The prevalence of obesity (BMI is more than or equal to 30 kg/m 2 ), diagnosed hypertension, diagnosed dyslipidemia, and diagnosed type 2 diabetes mellitus was respectively 23.6%, 12.2%, 17.4%, and 1.7%. Among survey participants, 34.5% were categorized as moderate and 43.6% as high CVD risk, according to American College of Sports Medicine guidelines. Conclusions: A high proportion of Québec firefighters are at moderate to high risk of CVD. These findings suggest that Québec fire departments should help all firefighters to adopt and maintain a healthy lifestyle.